TRANSFORMASI DIGITAL DI MASYARAKAT DESA : TANTANGAN DAN PELUANG MENUJU TERWUJUDNYA SDGS 2030 - Adellia Zahra; Agustini, Tini Dwi; Maudi Andari, Atikah Sari; Rachman, Ichsan Fauzi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Digital transformation plays a crucial role in advancing the Sustainable Development Goals (SDGs) by 2030, particularly in rural communities. This research, conducted through a literature review, explores the positive impacts of digital transformation in rural communities and analyzes the potential challenges in its implementation. The study finds that improving accessibility and connectivity of digital infrastructure, including internet access in rural areas, and developing adequate digital infrastructure are key challenges to realizing Digital Villages. However, opportunities such as empowering rural economies through local e-commerce and innovating public services using digital technology are also significant potentials that can support the development of Digital Villages. Additionally, the research identifies other challenges, such as infrastructure limitations and knowledge and skills gaps among rural communities, that need to be addressed in facing digital transformation in rural areas. By addressing these challenges and leveraging existing opportunities, rural communities can maximize the benefits of digital transformation to achieve sustainable development in the era of SDGs 2030.